Development and validation of a HPLC method for standardization of herbal and commercial extracts of Myrcia uniflora - Batista, Andrea N. de L. [UNESP]; Colombo, Renata [UNESP]; Pascoli, Inara C. de [UNESP]; Teles, Helder L. [UNESP]; Silva, Geraldo H. [UNESP]; Bomfim, Giovanni C. C. [UNESP]; Burgos, Rosilene C. R. [UNESP]; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Reimberg, Maria Célia H. (Sociedade Brasileira de Farmacognosia, 2011)
Myrcia uniflora Barb. Rodr., Myrtaceae, popularly known as pedra-hume-caá in Brazil, is sold as dry extracts in capsules or as tinctures for the treatment of diabetes mellitus. Previous phytochemical studies on this species described the occurrence of the flavonoids mearnsitrin and myricitrin. In the present study, the chromatographic profiles of M. uniflora leaves and commercial extracts were determined using HPLC-PAD. Myricitrin was used as an external standard in the development and validation of the HPLC method. The proposed method is simple, rapid and reliable and can be successfully applied in industry for standardization of herbs and phytomedicines commercialised in Brazil as pedra-hume-caá.
Keywords: Myrcia uniflora; pedra-hume-caá; HPLC; myricitrin; standardization